A video database of moving faces and people - O'Toole, A.J.; Harms, J.; Snow, S.L.; Hurst, D.R.; Pappas, M.R.; Ayyad, J.H.; Abdi, H. (IEEE transactions on pattern analysis and machine intelligence, 2005)
We describe a database of static images and video clips of human faces and people that is useful for testing algorithms for face and person recognition, head/eye tracking, and computer graphics modeling of natural human motions. For each person there are nine static "facial mug shots" and a series of video streams. The videos include a "moving facial mug shot," a facial speech clip, one or more dynamic facial expression clips, two gait videos, and a conversation video taken at a moderate distance from the camera. Complete data sets are available for 284 subjects and duplicate data sets, taken subsequent to the original set, are available for 229 subjects.